Institutional work by migrant women leaders in precarious spaces of volunteering in Melbourne, Australia. Issue 5 (4th May 2022) - Tsarenko, Yelena; Cruz, Angela Gracia B.; Snuggs, Elizabeth; Tojib, Dewi
Abstract: This paper analyses the role that migrant women leaders play in sustaining precarious spaces of community-led volunteering. The voluntary sector has been theorised as an interstitial yet connective space that nourishes unmet needs of migrant women in the context of familial demands, labour market marginalisation, and a diminishing welfare state. While state-funded initiatives are often intended to address these gendered asymmetries, less is known about the dynamics of precarious spaces of community-led volunteering, and in particular about the leaders who appreciate and navigate the complexities of these spaces. Grounding our analysis in feminist geographies of volunteering literature, and employing the concept of institutional work, we interview multiple stakeholders in a network of Local Migrant Women's Clubs (LMWCs) in Australia. In this precarious space, migrant women leaders are required to bridge contradictory logics of migrant women's vulnerabilities and escalating administrative expectations under poorly-resourced conditions. Our analysis advances institutional work as a productive frame to trace linkages between divergent institutional agendas at the macro-level, and the distributed agency and invisible labour of migrant women leaders at the level of lived experience. Overall, the lens of institutional work foregrounds the tacit and intensive investments required on the part of poorly resourced migrant women leaders to maintain required circulations of care in their local communities.